Optimizing Bogor Waqf Forest Through Community Development To Improve Welfare - Firdaus, Anisah; Wahyudi, Amin (UNIVERSITAS PAKUAN, 2017)
In addition to functioning for ecological conservation, Waqf forest also have the potential to support the community's economy. Many communities in and around forests still depend on forests for their livelihoods and benefits. However, deforestation or forest destruction has decreased the function of the forest. Waqf forests are built as an alternative strategy in overcoming forest deforestation. Optimization of waqf forest need to be carried out in order to improve the function of forests from an economic perspective to achieve community welfare. This research aims to examine the community development developed in Bogor waqf forest. The method applied in this research is descriptive qualitative approach with primary data sources from interviews, observation, and documentation. Meanwhile, secondary data sources from articles, books, web and blogs. The results showed that the implementation of community development in the Bogor waqf forest was not optimal due to technical constraints and natural factors. Therefore, alternative programs or activities needed to be developed to further improve the welfare of the community around the Bogor waqf forest.